Evidence-Based Practice in Hypertension Management: A Review of Acupressure, Progressive Muscle Relaxation, and Mobile Health Interventions - Jaya Kusuma, I Made; Suyasa, I Gede Putu Darma; Nuryanto, Kadek; Wulandari, Sarah Kartika (Babali Publisher, 2026)
Introduction: Despite the availability of pharmacological treatments, poor adherence and low patient awareness remain barriers to effective long-term management. Non-pharmacological interventions such as acupressure and progressive muscle relaxation (PMR) have demonstrated consistent benefits, yet broader implementation is limited by inadequate education, practical guidance, and patient engagement. Mobile health (mHealth) technologies offer opportunities for real-time monitoring and self-management support, but integrating complementary therapies into digital platforms remains underexplored. It aims to synthesize current evidence on the effectiveness of acupressure, progressive muscle relaxation (PMR), and mobile health (mHealth) interventions in enhancing self-management among individuals with hypertension.Methods: A narrative review with narrative synthesis was conducted in accordance with PRISMA 2020 and the PICOS framework. Searches were performed in PubMed, ProQuest, ScienceDirect, and Google Scholar using predefined keywords. No artificial intelligence (AI)–based tools were employed. Fifteen eligible studies were identified and thematically analyzed. The review included 15 eligible studies that examined non-pharmacological and digital interventions for hypertension management. Results: Specifically, three studies on acupressure explicitly reported significant reductions in systolic and diastolic blood pressure, while eight studies on progressive muscle relaxation (PMR), including multimodal formats combined with breathing exercises, music, or audiovisual support, consistently demonstrated improvements in blood pressure, stress, and sleep quality. In addition, three studies on mobile health (mHealth) interventions reported enhanced adherence, patient engagement, and self-monitoring behaviors. One additional study investigated acupuncture (needle-based stimulation rather than manual acupressure); this study was retained for completeness but not synthesized with the primary findings due to differences in intervention characteristics.Conclusion: Overall, although strong evidence supports the effectiveness of acupressure, PMR, and mHealth individually, none of the included studies integrated acupressure and PMR within a single mHealth platform, underscoring a critical gap in digital hypertension management research.